Ferroelectrics: MXene‐Derived Ferroelectric Crystals (Adv. Mater. 14/2019) - Tu, Shaobo; Ming, Fangwang; Zhang, Junwei; Zhang, Xixiang; Alshareef, Husam N. (Advanced materials (Weinheim), 2019)
In article number 1806860, Xixiang Zhang, Husam N. Alshareef, and co‐workers develop a process to derive KNbO3 ferroelectric crystals from two‐dimensional MXenes with excellent ferroelectric properties. The plate‐like ferroelectric crystals with c‐axis orientation inherit their morphology thanks to the two‐dimensional nature of the MXene precursor. KNbO3 is a very interesting material because it exhibits electro‐optic properties, making it useful in waveguide and holography applications.